A comparison of the influences of different training approaches on trainees' perceptions of self-efficacy to achieve training outcomes - Huang, Wen-Rou (2015)
The evaluation of the effectiveness of training approaches has received great attention in recent years. Self efficacy was proposed to be one of the training outcomes in evaluation. In this study, the influences of structured on-the-job training and classroom training approaches on trainees' perceptions of selfefficacy to achieve training outcomes was explored. Moreover, the relationships among the variables of trainees' general self-efficacy, self-efficacy to achieve training outcomes and two training approaches have also been discussed. This study was conducted by survey in the Training and Development Center of the Taiwan Academy of Banking and Finance. The findings indicated the structured on-the-job training approach can generate greater self-efficacy to achieve training outcomes than classroom training (lecture), especially for trainees with low general self-efficacy. In addition, it was also found that there is a positive relationship between the trainees' general self-efficacy and their self-efficacy to achieve the trailling outcomes.